MIGRATION TRADITION AND FAMILY ECONOMIC EMPOWERMENT: A CASE STUDY OF THE MINANGKABAU COMMUNITY FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Jimmi Saputra; Rizal Fahlefi; Ahmad Lutfi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The migration tradition is an integral part of Minangkabau identity, intertwining customary values, religious principles, and family economic strategies. This study aims to analyze the role of the migration tradition in strengthening family economics from an Islamic economic perspective. Using a qualitative case study approach with six migrant informants, data were collected through in-depth interviews and participatory observation, and analyzed using the Miles and Huberman interactive model. The findings reveal that migration is driven by religious motivation, family responsibility, and an Islamic work ethic grounded in the principles of kasb (lawful earning), maslahah, and tawazun. Migrant activities—including remittance sending and involvement in social organizations—significantly enhance family welfare, reinforce social solidarity, and preserve customary and religious values. The synthesis of findings indicates that the Minangkabau migration tradition forms a community-based moral economic model that is harmonious, sustainable, and rooted in Islamic economic principles